The Role of Civil Society in the War of Indonesia Independence : A Case Study in the Battle Against the Allied Forces In Sukabumi 1945-1946 - Sulasman, Sulasman (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The revolution of Sukabumi is closely related to the role of many kyai, ulama and pesantren’s leaders in its process. They had great power to encourage people’s spirit and emotion. This success was gained by using their religious language to communicate. They used the concept of jihad fi sabilillah. The climax of the revolution is the battle against the invader’s alliance along the road of Cigombong– Ciranjang that was followed by a series of battle,such as Bojongkokosan battle,causing the bombing of Cibadak by Alliance air force; Gekbrong battle; and general attack involving army force, ulama, people’s organization and the students of pesantrens.